Ash-burn test according to ISO 3340 for the evaluation of the abrasive effect of particleboard on cutting tools. Issue 2 (4th March 2022) - Patsch, Richard; Frömel-Frybort, Stephan; Stanzl-Tschegg, Stefanie E.
ABSTRACT: The mineral content of particleboard (PB) is suspected to be one of the main factors influencing cutting-tool life. The aim of this study was therefore to investigate the influence of the mineral content of PBs on tool life as a function of the mineral content and the size of the largest sand grains. The mineral content of PB according to ISO 3340 was used as a value for the abrasiveness. Different samples of PB were analysed by comparison of the mineral content and the lifetime of a tungsten-carbide knife. In addition, the maximum size of the mineral grains in comparison with the total amount of mineral content was studied. The investigation showed that the mineral content of the PB and maximum sand-grain size are not sufficient to predict tool life. In comparison with the result of a lifetime test, which directly measures the wear behaviour of a board, the treatment of the ashes with hydrochloric acid after combustion, according to ISO 3340, destroys abrasive ingredients in the PB; therefore, this method is not suitable for identifying all abrasive components of a PB.